Interrupted Lives: Racism and Maternal Mortality Among Black Women in Brazil - Souza, Camila Aparecida Siqueira; Reis, Jackson Santos dos; Tessarolo, Mariana Medeiros Mota; Ferreira, Luiz Carlos; Soares, Andrea Pereira Diniz; Ferreira, José Paulo da Silva; Ewerton Naves Dias (Periódicos Brasil. Pesquisa Científica, 2026)
Introduction: Maternal mortality in Brazil remains high and reflects health inequities, with a greater risk of death among Black women, associated with mechanisms of structural, institutional, and interpersonal racism that affect access, quality of care, and health surveillance. Objective: To analyze how racism is related to maternal mortality among Black women in Brazil through a literature review. Method: An integrative review was conducted using searches in the Virtual Health Library (VHL) and Google Scholar, applying DeCS descriptors and inclusion/exclusion criteria, followed by standardized data extraction, critical appraisal, and thematic synthesis of eligible studies. Results: Thirteen studies (2006-2025) were included. The evidence converged into four themes: (1) Structural, institutional, and interpersonal racism as determinants of the risk of maternal death, including the invisibility of the race/color variable and biases in clinical practice; (2) Quality of care and obstetric violence during prenatal care, childbirth, and the postpartum period, with communication failures, reduced autonomy, and unequal pain management; (3) Access and care barriers within the Health Care Network, including delays, care-seeking peregrination, and discontinuity of care; (4) Surveillance and public policies, highlighting the importance of qualified recordkeeping, timely investigation of deaths, and equity targets to drive change. Conclusion: Racism is related to maternal mortality among Black women by producing and sustaining barriers to access, worsening the quality of care, and contributing to monitoring failures, thereby increasing the occurrence of preventable outcomes. To address this problem, the literature indicates consistent and measurable actions: improving and using the race/color variable, reducing delays in care through care pathways and target response times, strengthening respectful care practices (including communication, consent, and adequate pain management), and consolidating surveillance with accountability and explicit equity goals.